2014
DOI: 10.1371/journal.pone.0104300
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Prevalence and Awareness Rates of Hypertension in Africa: A Systematic Analysis

Abstract: BackgroundThe burden of hypertension is high in Africa, and due to rapid population growth and ageing, the exact burden on the continent is still far from being known. We aimed to estimate the prevalence and awareness rates of hypertension in Africa based on the cut off “≥140/90 mm Hg”.MethodsWe conducted a systematic search of Medline, EMBASE and Global Health. Search date was set from January 1980 to December 2013. We included population-based studies on hypertension, conducted among people aged ≥15 years an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
240
7
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 247 publications
(276 citation statements)
references
References 91 publications
27
240
7
2
Order By: Relevance
“…So was knowledge about hypertension determinants high in Germany [3] opposed to findings in Africa with lower rate of awareness [4]. Awareness rate remains low despite increasing prevalence of HTN [5]. Further some studies found improvements in awareness similar among people who had or did not have cardiovascular comorbidities [6].…”
Section: Introductionmentioning
confidence: 99%
“…So was knowledge about hypertension determinants high in Germany [3] opposed to findings in Africa with lower rate of awareness [4]. Awareness rate remains low despite increasing prevalence of HTN [5]. Further some studies found improvements in awareness similar among people who had or did not have cardiovascular comorbidities [6].…”
Section: Introductionmentioning
confidence: 99%
“…3), a reflection of a maximal care gap. [5][6][7][8] In 2011, UN member states acknowledged at the highest international level that premature deaths from NCDs reduce productivity and curtail economic growth, causing significant social challenges in most countries. 9 In 2015, the previous target of 25% reduction in rate of premature mortality from NCDs by 2025 was extended to a reduction of 33% by 2030, through prevention, treatment and promotion of mental health and wellbeing.…”
Section: Recheck and Review Readings In 4 Weeksmentioning
confidence: 99%
“…Anecdotal reports estimate that every Nigerian knows or is related to somebody who has had a stroke before [16]. Studies from other African countries estimated stroke crude incidence rates ranging from 31/100 000 per year in Harare, Zimbabwe in 1998 [17] to 149/100 000 per year in Maputo, Mozambique in 2006 [18][19][20]. Crude prevalence rate of stroke in urban Nigeria is 1.14/1000 (males 1.51, females 0.69) [21].…”
Section: Epidemiology Of Stroke In Africamentioning
confidence: 99%